Digital survey in religious architecture. Methodologies for the studying of two monasteries in Alentejo region close to the UNESCO heritage site of Èvora (Portugal) - Bertocci, S.; Bigongiari, M.; Pivetta, M.; Cioli, F.; Becherini, P.; Volzone, R. (Il Simposio UID di internazionalizzazione della ricerca. Patrimoni culturali, Architettura, Paesaggio e Design tra ricerca e sperimentazione didattica, 2019)
Santa Catarina de Montemuro and Santa Margarida do Aivado monasteries belong to the eremitical congregation of São Paulo da Serra de Ossa, and are located in Alentejo Region, close to the UNESCO Heritage Site of Évora (Portugal). The first one, is the evolution of the hermitage Montemuro, documented since 1415 around Évora (Portugal), and abandoned in 1593. The second one, is originated in the hermitage Aivado, founded in 1406 and abandoned in 1797. The study of the monasteries, due to lack of architectural survey, required a digital survey campaign that integrates the morphological data coming from laser scanners with the information about the characteristics of the materials, this one acquired through the use of Structure from Motion (SFM) methodologies.